Diary of a man in despair - Reck-Malleczewen, Friedrich Percyval (2013)
Friedrich Reck might seem an unlikely rebel against Nazism. Not just a conservative but a rock-ribbed reactionary, he played the part of a landed gentleman, deplored democracy, and rejected the modern world outright. To Reck the Nazis were ruthless revolutionaries in Gothic drag, and helpless as he was to counter the spell they had cast on the German people, he felt compelled to record the corruptions of their rule. The result is less a diary than a sequence of stark and astonishing snapshots of life in Germany between 1936 and 1944. We see the Nazis at the peak of power, and the murderous panic with which they respond to approaching defeat; their travesty of traditional folkways in the name of the Volk; and the author's own missed opportunity to shoot Hitler.